Flexible Organic Electrochemical Transistors for Highly Selective Enzyme Biosensors and Used for Saliva Testing. (2nd December 2014) - Liao, Caizhi; Mak, Chunhin; Zhang, Meng; Chan, Helen L. W.; Yan, Feng
<x xml:space="preserve">Abstract</x> Flexible organic electrochemical transistors (OECTs) are successfully used as high‐performance enzyme biosensors, such as uric acid (UA) and cholesterol sensors. The sensitivity and selectivity of the sensors can be simultaneously enhanced by co‐modifying the gate electrodes with positively/negatively charged bilayer polymer films and enzymes. These OECT‐based UA sensors are successfully utilized for non‐invasive UA detection in human saliva. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>